2014
DOI: 10.5194/acp-14-115-2014
|View full text |Cite
|
Sign up to set email alerts
|

Summertime free-tropospheric ozone pool over the eastern Mediterranean/Middle East

Abstract: Abstract.Observations show that the Mediterranean troposphere is characterized by a marked enhancement in summertime ozone, with a maximum over the eastern Mediterranean. This has been linked to enhanced photochemical ozone production and subsidence under cloud-free anticyclonic conditions. The eastern Mediterranean is among the regions with the highest levels of background tropospheric ozone worldwide. A 12 yr climatological analysis (1998-2009) of free-tropospheric ozone was carried out over the region based… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(100 citation statements)
references
References 71 publications
7
91
1
1
Order By: Relevance
“…Variability in climate, such as the North Atlantic Oscillation (NAO), contributes to the variation in O 3 concentrations in the upper troposphere through variations both in the stratospheric contribution and in the transport patterns (Gaudel et al, 2015). Although the stratospheric contribution to the O 3 concentrations at the surface is generally small (3-5 ppb(v)) in Europe (Lelieveld and Dentener, 2000), it can be a relevant contribution to near-surface O 3 in certain areas and time periods (Zanis et al, 2014) and could affect the observed trend in near-surface O 3 (e.g., Fusco and Logan, 2003). Despite the large number of studies of tropospheric O 3 , a number of challenges still remain, such as explaining the near-surface concentration trends (Monks et al, 2015).…”
Section: Andersson Et Al: Reanalysis Of and Attribution To Near-smentioning
confidence: 99%
“…Variability in climate, such as the North Atlantic Oscillation (NAO), contributes to the variation in O 3 concentrations in the upper troposphere through variations both in the stratospheric contribution and in the transport patterns (Gaudel et al, 2015). Although the stratospheric contribution to the O 3 concentrations at the surface is generally small (3-5 ppb(v)) in Europe (Lelieveld and Dentener, 2000), it can be a relevant contribution to near-surface O 3 in certain areas and time periods (Zanis et al, 2014) and could affect the observed trend in near-surface O 3 (e.g., Fusco and Logan, 2003). Despite the large number of studies of tropospheric O 3 , a number of challenges still remain, such as explaining the near-surface concentration trends (Monks et al, 2015).…”
Section: Andersson Et Al: Reanalysis Of and Attribution To Near-smentioning
confidence: 99%
“…In highly dynamic regions such as the Mediterranean Basin (Lelieveld et al, 2002(Lelieveld et al, , 2009, the strength of the meteorological systems (Azores anticyclone and Middle Eastern depression) are key factors in explaining both the variability and the anomalies of ozone in the lower troposphere in this region . Recent observations have suggested there is a summertime free-tropospheric ozone pool over the Mediterranean (Zanis et al, 2014;Kalabokas et al, 2013). The data in Fig.…”
Section: A Climatological View Of Ozone/linkages Across the Scalesmentioning
confidence: 99%
“…1). The enhancement of TOC is similar in magnitude as TOC enhancements observed during the follow events: (1) the wellknown biomass burning plume in the Southern Hemisphere that was transported over the South Atlantic, the coast of South Africa, along the Indian Ocean and towards Australia (e.g., Fishman et al, 1986Fishman et al, , 1991; (2) TOC attributed to anthropogenic sources in the Northern Hemisphere, for instance northern India; and (3) the Mediterranean summer ozone pool attributed to the stratospheric-tropospheric exchange (STE) (Zanis et al, 2014). A spring (or so-called pre-monsoon; see Sect.…”
Section: Introductionmentioning
confidence: 99%